Marx @ 200: Debating Capitalism & Perspectives for the Future of Radical Theory (combined PDF of all articles) - Christian Fuchs; Lara Monticelli (tripleC: Communication, Capitalism & Critique)
Combined pdf of all articles published in the special issue "Marx @ 200: Debating Capitalism & Perspectives for the Future of Radical Theory", edited by Christian Fuchs and Lara Monticelli, tripleC: Communication, Capitalism & Critique 16 (2), 2018, pp. 406-741.